Patrimônio + educação, políticas de gestão: novas perspectivas, largas possibilidades - Paula Gomes Cury (2012)
The present work investigates Heritage Educational policies in Brazil, in relation to public policies on the preservation and valuation of heritages, as well as managerial policies from contemporary urban planning. A recognition that the notion of Heritage has been transformed due to a series of factors related to the situation forged in the cities throughout the centuries implies the revision of its assumptions and concepts. This contemporary notion, reached more precisely over the last century, is the one responsible for introducing comprehensive procedures of heritage identification and recognition and, so, more inclusive with respect to cultural diversity, impacting particularly on the issue of rights and citizenship in relation to cultural production. For this reason, access to cultural heritage as well as its fruition and recognition are prevailing practices on heritage education projectsand that are analysed in the light of theories from the field of Education and Heritage, as well as those arising from the practice of management that meets the complex worldof culture and the cities. Thereafter, we seek to discuss and thus reveal a closer relationship between these fields, highlighting their correlations. New perspectives marked by the processes of expansion and renewal of its concepts urge, in the case of heritage education, broad possibilities for dialogue and mutual contribution. Finally, the challenges prominent in the contemporary world are discussed, given its impacts on educational activities linked to heritage and on its managemen policies.